2018
DOI: 10.1002/hed.25431
|View full text |Cite
|
Sign up to set email alerts
|

Use of MRI and FDG‐PET/CT to predict fixation of advanced hypopharyngeal squamous cell carcinoma to prevertebral space

Abstract: Background We evaluated the ability of different (18F)fluoro‐deoxy‐d‐glucose (FDG)‐positron emission tomography (PET)‐based and magnetic resonance (MR)‐based parameters to identify prevertebral space (PVS) infiltration by hypopharyngeal carcinoma. Methods Retrospective study on 59 patients with advanced hypopharyngeal squamous cell carcinoma undergoing cross‐sectional imaging and triple endoscopy for staging. Results Obliteration of retropharyngeal fat plane on T1‐weighted MR images was found more often (P < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Over the past 20 years, the literature has focused primarily on CT and MRI sometimes combined with PET to detect prevertebral fascia invasion. [5][6][7] Although there is anecdotal evidence suggesting that esophagrams also have diagnostic utility, to our knowledge there are no data to support it. Nonetheless, in conjunction with other modalities, our institution has still used esophagrams to evaluate prevertebral fascia fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, the literature has focused primarily on CT and MRI sometimes combined with PET to detect prevertebral fascia invasion. [5][6][7] Although there is anecdotal evidence suggesting that esophagrams also have diagnostic utility, to our knowledge there are no data to support it. Nonetheless, in conjunction with other modalities, our institution has still used esophagrams to evaluate prevertebral fascia fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Specific acquisition parameters have been published previously. 16,17 All PET scans were carried out at our institution and covered the entire head as part of the default imaging protocol.…”
Section: Pet/ct Acquisitionmentioning
confidence: 99%
“…Among these studies, Meerwein and colleagues evaluated tumor fixation to the prevertebral space in 59 patients with advanced SCC of the hypopharynx. 46 Neoplastic invasion of the prevertebral space renders a tumor unresectable; prevertebral space invasion can be diagnosed by exploratory cervicotomy or by palpation during panendoscopy. Both the MR imaging feature "complete obliteration of the retropharyngeal fat" and the combination of PET-based parameters "focal FDG uptake of prevertebral muscles and increased SUV max of the primary tumor" independently predicted fixation to the prevertebral space with an accuracy of 98%.…”
Section: Staging Of Primary Head and Neck Squamous Cell Carcinoma Loc...mentioning
confidence: 99%
“…Both the MR imaging feature "complete obliteration of the retropharyngeal fat" and the combination of PET-based parameters "focal FDG uptake of prevertebral muscles and increased SUV max of the primary tumor" independently predicted fixation to the prevertebral space with an accuracy of 98%. 46 In a series of 58 patients with primary and recurrent HNSCC, Sekine and colleagues evaluated further factors affecting local tumor resectability (eg, invasion of the mediastinum, mandible and laryngeal cartilages, or perineural spread [PNS]) and found that both contrast-enhanced PET/CT and PET/MR imaging with a fully diagnostic regional MR imaging protocol (but without DWI or perfusion imaging) performed equally well, although there was a slight but nonsignificant trend toward more accurate results with PET/MR imaging. 47 The standard of reference in this study consisted in clinical findings, intraoperative results and/or histopathology, which was, however, available only in 51% of cases.…”
Section: Staging Of Primary Head and Neck Squamous Cell Carcinoma Loc...mentioning
confidence: 99%